Consent for medical treatment of trans youth - Jowett, Steph, 1991- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
Access to medical treatment for trans youth occupies a haphazard and dynamic legal landscape. In this comprehensive scholarly analysis of the historical and current legal principles, Steph Jowett examines the medico-legal nexus of regulation of this healthcare in Australia and in England and Wales. This is informed by an in-depth discussion of the medical literature on treatment for trans youth, including clinical guidelines, the outcomes of treatment and outcomes for trans youth who are unable to be treated. With illustrative examples and clear language, Jowett argues that legal barriers to clinical practice should be congruent with and reflect the current state of medical knowledge. Not only does Jowett assess the extent to which key legal decisions have been consistent with medical knowledge in the past, but she offers a nuanced, comparative perspective that will inform reform efforts in the future.
Introduction -- Gender diversity in children and adolescents -- Medical treatment of trans youth -- Australian law governing consent to medical treatment for trans youth -- Law governing consent to medical treatment for trans youth in England and Wales -- Comparison of the law in England and Wales with Australia -- Congruency of the law with medicine -- Future directions for law reform.
Title from publisher's bibliographic system (viewed on 04 Oct 2022).
Keywords: Informed consent (Medical law) -- Great Britain; Informed consent (Medical law) -- Australia; Transsexual youth -- Medical care -- Law and legislation -- Great Britain; Transsexual youth -- Medical care -- Law and legislation -- Australia; Gender-nonconforming youth -- Medical care -- Law and legislation -- Great Britain; Gender-nonconforming youth -- Medical care -- Law and legislation -- Australia; Gender identity -- Law and legislation -- Great Britain; Gender identity -- Law and legislation -- Australia